ANALISIS PERBANDINGAN BAHAN AJAR "HANYU 2" TERBITAN UNIVERSITAS JINAN EDISI TAHUN 2000 DENGAN EDISI TAHUN 2007 - Bualin, Remilini Megati; Ina, Ina; Afrimonika, Yoanna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
In Chinese teaching, there are three factors: teachers, students, and teaching materials. In the process of teaching Chinese, textbooks are one of the most important factors. Textbooks are the bridge connecting teachers and students. According to the ability of the students, it is very important to choose the right teaching materials. The purpose of this study is to compare the 2000 publication and the 2007 publication of Hanyu 2 published by Jinan University to find out the strengths and weaknesses of the textbook so that teachers can utilize the textbook to stimulate students' interest and thinking, adjust their teaching methods, and improve the quality of learning. The main research object is the twenty six student of Suster junior high school and twenty student of YPK junior high school and their mandarin teacher. In addition, the questionnaire method is used to collect students' evaluation of the textbook, the author conducts interviews with teachers to obtain data, and the analysts method is used to analyses the difference of the book. The author conducted a literature research and found that the 2007 edition of Hanyu 2 has more vocabularies. The 2000 edition of Hanyu 2 contains short essays, while the 2007 edition of Hanyu 2 contains short essays and dialogues. The 2007 edition of Hanyu 2 has specific grammatical explanations. The 2007 edition of Hanyu 2 had poor reading passages and storylines. Teachers thought the book had grammatical explanations and example sentences. Teachers found the textbook easy to use, but they found it difficult to explain vocabulary due to the lack of explanations of pinyin and numbered auxiliary words. Students found the materials in Chinese 2 interesting and suitable to use. The impact of the materials on daily life was also good